1995
DOI: 10.1111/j.1600-9657.1995.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Observation of bacteria and fungi in infected root canals and dentinal tubules by SEM

Abstract: The aim of this study was to observe the root canal flora and possible penetration of microorganisms into dentinal tubules in teeth with necrotic pulps. Ten infected maxillary and mandibular molars with periapical lesions were extracted and fixed in 2.5% phosphate-buffered glutaraldehyde solution for nine days. After separation from the crowns, longitudinal grooves were cut in the roots, and they were split into two halves. The specimens were prepared for SEM. The root canals and the dentinal tubules of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
1
15

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(181 citation statements)
references
References 14 publications
10
151
1
15
Order By: Relevance
“…In previous SEM studies, bacteria have been observed colonizing the periapical tissues (17,18) and root canal (9,19). In some of these studies, structures typical of bacterial colonization have been observed, including filaments that seem to hold the bacteria to each other or to the dentin surface (18) and an amorphous material, presumably polysaccharide, covering the bacteria (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous SEM studies, bacteria have been observed colonizing the periapical tissues (17,18) and root canal (9,19). In some of these studies, structures typical of bacterial colonization have been observed, including filaments that seem to hold the bacteria to each other or to the dentin surface (18) and an amorphous material, presumably polysaccharide, covering the bacteria (17).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal grooves were cut along the entire length of each root. The roots were then split with a hammer and chisel into two halves as described by Sen et al (9). Each root half was then gently washed in 0.2 M potassium phosphate buffer (PBS), pH 7.2, at 4°C to 6°C.…”
Section: Sem Analysismentioning
confidence: 99%
“…Several studies have revealed the presence of fungi in endodontic infections. Sen et al (4) used scanning electronic microscopy (SEM) to observe bacteria and fungi in root canals and dentinal tubules of teeth with endodontic infection, revealing the presence of fungi in 4 out of 10 teeth. Yeasts were identified by microscopic exploration of single cells, either spherical or oval, measuring 4-6 mm in diameter.…”
Section: In Vitro Susceptibility Of Oral Candida Albicansmentioning
confidence: 99%
“…Penetration of bacteria into the dentinal tubules has been reported to range from 10 to 300 m. 9,42 Despite the controversy regarding the effect of the smear layer on the bacterial colonization of the dentinal tubules 43,44 and because the smear layer itself can be contaminated and has the potential to protect bacteria within the dentinal tubules, it is sensible to remove the smear layer and allow disinfection of the entire root canal system. 45 Although NaOCl is efficient in dissolving organic components of the smear layer, its ability to remove inorganic components is limited.…”
mentioning
confidence: 99%